Developmeny Of A Visual Display As A Monitoring System To Calculate Overall Equipment Effectiveness (OEE) - Lee, Yee Von (Universiti Sains Malaysia, 2017)
In global manufacturing, manufacturers from different nations strive to improve their performance by enhancing their manufacturing productivity than another to maintain a competitive advantage in this harsh business environment. Many manufacturers have adopted different kinds of manufacturing tools and methods such as Overall equipment effectiveness, OEE to make improvements in the productivity. OEE is a standardized performance indicator used in manufacturing that allows the manufacturers to measure the effectiveness and efficiency of a particular equipment used in the production shop floor. OEE is a top view metric on the quality, availability and performance of an equipment. It can be used in further analysis by identifying the reasons or losses behind the poor performance of a particular equipment. This paper will present the development of a visual display as a monitoring system to calculate OEE. The objective of this study is to automate the OEE calculation and to develop a visual display of OEE as monitoring system. The development plays an important role because it is able to save the time for analyzing and identifying the underlying losses. Besides, it helps to track the trend of OEE of a particular equipment from time to time in a line chart to observe the performance. The outcome of this paper will provide methodology of developing visual display OEE as monitoring system by using Visual Basic Application, VBA.